INTERPRETAÇÃO DAS NORMAS E RESPONSABILIDADE DO JUIZ – ENTRE REMINISCÊNCIAS HISTÓRICAS E PERSPECTIVAS FUTURAS - Landi, Andrea (Revista da AJURIS - Qualis A2, 2016)
INTERPRETATION OF LEGAL RULES AND RESPONSIBILITIES OF THE JUDGE – HISTORICAL REMINISCENCES AND FUTURE PERSPECTIVES RESUMO: A responsabilidade do juiz por errônea interpretação das normas foi um tema de particular importância no Direito Comum e permanecesse sendo naqueles ordenamentos que ainda o seguem, onde o direito vigente deve levar em consideração o relevante aporte nomopoiético da doutrina. A simbiose dialética entre juristas e juízes, que ali se realiza através do mecanismo da communis opinio doctorum vinculante para o juiz, pode constituir um momento de reflexão sobre aspectos atuais da jurisdição nos ordenamentos de direito codificado, sobretudo para desvelar a inconsistência de alguns mitos da modernidade, como a estatalidade do direito, o formalismo e o silogismo judicial. PALAVRAS-CHAVE: interpretação judicial; direito comum medieval; communis opinio doctorum. ABSTRACT: The judge's responsibility for erroneous interpretation of the legal rules was a subject of particular importance in the ius commune and remain being in those jurisdictions which still follow this approach to law, where the applicable law should take into consideration the relevant contribution of the doctrine. The dialectic symbiosis between jurists and judges, which takes place through the mechanism of the opinio communis doctorum, binding to the judge, may be a moment of reflection on current aspects of jurisdiction in codified law systems, especially for unveiling the inconsistency of some myths of modernity, such as the statality of the law, the formalism and the legal syllogism. KEYWORDS: judicial interpretation; medieval ius commune; opinio communis doctorum. SUMÁRIO: 1 A interpretação das normas; 2 A solução do Direito Comum; 3 Algumas perspectivas atuais. SUMMARY: 1 Legal interpretation; 2 The ius commune solution; 3 Some current perspectives.